Evaluation of the effectiveness of medical therapy versus surgical intervention in pediatric recurrent acute otitis media - Trinh, Nguyen Thi Dieu; Hung, Dang Ngoc; Tri, Ho Minh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Objective: To evaluate the clinical and subclinical characteristics and the effectiveness of different treatment methods in children with recurrent acute otitis media (RAOM). Methods: This was a descriptive interventional study conducted on 61 children diagnosed with RAOM and treated at Hue University of Medicine and Pharmacy Hospital and Hue Central Hospital from March 2023 to May 2025. Treatment methods included medical therapy during acute episodes, adenoidectomy, and adenoidectomy combined with tympanostomy tube insertion (TTI). Treatment effectiveness was assessed based on the number of recurrent episodes, recurrence rate, and time to next recurrence within 6 months after treatment. Results: The mean age was 34.48 ± 28.42 months, with a male predominance (65.6%). Most children presented with fever and ear pain. Children who developed the disease before 6 months of age and those attending daycare before the age of 1 had significantly more recurrent episodes (p < 0.05). The degree of adenoid hypertrophy was significantly associated with abnormal tympanometry type. After 6 months of treatment, the surgical group had a significantly higher rate of non-recurrence compared to the medical treatment group (p < 0.05). The average number of recurrences after 6 months was significantly higher in the medical treatment group (p < 0.05). The time to the next recurrence was significantly longer in the surgical intervention group compared to the medical group (p < 0.05). Conclusion: Adenoidectomy with or without tympanostomy tube insertion is associated with more favorable short-term outcomes, including a lower number of recurrent episodes and a prolonged time to recurrence, compared to medical therapy in children with RAOM. However, due to the non-randomized design, these findings should be interpreted with caution.